2u(u-4)=0

Simple and best practice solution for 2u(u-4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2u(u-4)=0 equation:


Simplifying
2u(u + -4) = 0

Reorder the terms:
2u(-4 + u) = 0
(-4 * 2u + u * 2u) = 0
(-8u + 2u2) = 0

Solving
-8u + 2u2 = 0

Solving for variable 'u'.

Factor out the Greatest Common Factor (GCF), '2u'.
2u(-4 + u) = 0

Ignore the factor 2.

Subproblem 1

Set the factor 'u' equal to zero and attempt to solve: Simplifying u = 0 Solving u = 0 Move all terms containing u to the left, all other terms to the right. Simplifying u = 0

Subproblem 2

Set the factor '(-4 + u)' equal to zero and attempt to solve: Simplifying -4 + u = 0 Solving -4 + u = 0 Move all terms containing u to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + u = 0 + 4 Combine like terms: -4 + 4 = 0 0 + u = 0 + 4 u = 0 + 4 Combine like terms: 0 + 4 = 4 u = 4 Simplifying u = 4

Solution

u = {0, 4}

See similar equations:

| 2(7x-8)+5=14x-11 | | (16-8)3+22/11= | | (5d-7)(7d+2)=0 | | d+12=20-3d | | x-4.3=23 | | p(p+7)=0 | | -24s+-53=39+-s | | (t-8)(t-5)=0 | | 7x+6-3x=13x+17 | | x-4.3=19 | | -1-2=3y | | -54=-4(3n+1)+2n | | (7v+3)(7v+9)=0 | | y=-2x^5+16x^4+66x^3 | | z^2-5z+7+z=0 | | 15z^2+7z-16=0 | | g(9g+7)=0 | | 8x+8=38 | | x+8.8=33 | | .80x+.85(40)=.40(75) | | (f-8)(8f-5)=0 | | 7x+3-2x+9-5x=19 | | (1+2i)(1-2i)=0 | | 2.25=-2.67x-1.83x | | 8a+11=3a+41 | | x+7.7=33 | | (r-8)(r+1)=0 | | x-25=-65 | | 6(r-4)=-5r+31 | | y=10x^4-360x^2 | | (k-8)(k+2)=0 | | x^2+bx+c=r |

Equations solver categories